Can benefit appeals and social norms in reminder letters persuade self-employed mental healthcare professionals to report their waiting times to a regulatory agency? - Tess J. Beke; Jorieke E. Moorlag; Rick B. van Baaren; Barbara C.N. Müller (Social Influence)
Mental healthcare professionals in the Netherlands are required to report waiting times to the healthcare regulator but often fail to comply. This study examines whether reminder letters using benefit appeals or social norms increase the intention to report waiting times and whether resistance to change influences this intention. A total of 440 self-employed mental healthcare professionals received one of four types of letters (social norm, no norm, self-benefit, other-benefit) or no letter. Results showed no significant impact of reminders on intentions. However, two types of resistance—skepticism and inertia – were identified as predictors of intention. These findings contribute to understanding behavioral resistance and offer guidance for improving compliance with reporting requirements.